The research of composer’s creativity in the context of modern Azerbaijani music - Kamala Vais, Aleskerli (Opción, 2020)
The study aims to investigate the spread of the main directions of the Western avant-garde in Azerbaijani music and the study of Khayyam Mirzazade’s style of the author in the artistic context via comparative qualitative research methods. As a result, the evolution of style is the cause of changes that occur in the process of formation composer’s style and its evolution. In conclusion, innovations that occur in the composer’s work during the evolution which is the process of natural creativity, show the continuity of his development as a creative personality.